Motivation of athletes: individual and group running lessons - Zashchirinskaya O.V.; Ilina N.L.; Arkhipova E.V.; Medina N.A. Bracamonte (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the reasons why people participate in sports, focusing on both group and individual training running sessions. Methods and structure of the study. The research involved 93 amateur runners, ranging in age from 19 to 69. The participants were divided into two groups: those who studied in a group (42 individuals) and those who studied individually with a coach (51 individuals). All athletes underwent a survey using the methodology «Assessment of the Motives of an Amateur Athlete (Motivation Scale for Motor Activity, FASHION)» in adaptation by K.A. Bochaver, D.V. Bondarev, M.A. Papkov, and the author’s questionnaire for analyzing biographical data of the subjects’ motivational attitudes. Results and conclusions. The reasons why amateur runners consistently engage in training have been explored, and the relationship between motivation and the type of training has been examined, particularly in the context of the growing popularity of marathon and race participation, particularly in St. Petersburg, where the number of athletes participating is increasing year after year. It was discovered that there were differences in the scale of «Group affiliation» between athletes who trained individually and those who trained in a group. Additionally, there were variations in the factors that maintained motivation and the ultimate objectives of their training. Despite the diverse and individual motivations for running, there are commonalities that unite runners into a community, regardless of their personal motivational priorities.